El Niño Pacing Orchestrates Inter‐Basin Pacific‐Indian Ocean Interannual Connections. Issue 19 (7th October 2021) - Jiang, Feng; Zhang, Wenjun; Jin, Fei‐Fei; Stuecker, Malte F.; Allan, Rob
Abstract: El Niño‐Southern Oscillation (ENSO), the primary source of year‐to‐year climate variability on Earth, has profound impacts on the Indian Ocean dipole (IOD), another important climate pattern. Much attention has been paid to potentially increased ENSO predictability by utilizing IOD conditions, inferred from a statistically significant correlation with ENSO at a long lead time. However, the intrinsic dynamics for the causality of this IOD‐ENSO relationship remain largely elusive. Here, we demonstrate that the observed nonstationary IOD‐ENSO lead‐lag relationship is mainly ENSO‐driven and therefore adds no additional information for ENSO predictability. The nonstationarity of their correlation is a manifestation of ENSO cycle complexity. Multi‐climate model and theoretical results further demonstrate that ENSO pacing tightly controls the statistical IOD‐ENSO relationship via changes in ENSO periodicity and regularity. This highlights that ENSO dominates the inter‐basin Pacific‐Indian Ocean interactions, shedding light on the key predictors for interannual pantropical climate variability. Plain Language Summary: Mounting attention has been paid to finding potential predictability sources outside the tropical Pacific to extend the prediction horizon of the El Niño‐Southern Oscillation (ENSO). This study shows that the observed inter‐basin lead‐lag relationship in the Indo‐Pacific, that was previously invoked to identify the Indian Ocean dipole as an independent predictor of ENSO, is in fact a manifestation of ENSO cycle complexity. We demonstrate that ENSO pacing tightly controls the inter‐basin Pacific‐Indian Ocean interannual relationship via changes in fundamental ENSO properties. The causal relationship identified here regarding inter‐basin climate interactions is of crucial relevance for future studies investigating pantropical climate interactions. Key Points: The observed Indian Ocean dipole (IOD)‐El Niño‐Southern Oscillation (ENSO) lead‐lag relationship is primarily ENSO‐driven, which adds no additional information to ENSO predictability The observed nonstationarity of inter‐basin Pacific‐Indian Ocean interannual connectivity is a manifestation of ENSO cycle complexity ENSO pacing regulates the IOD‐ENSO relationship via changes in fundamental ENSO properties